Will tropical mountaintop plant species survive climate change? Identifying key knowledge gaps using species distribution modelling in Australia. (November 2015) - Costion, Craig M.; Simpson, Lalita; Pert, Petina L.; Carlsen, Monica M.; John Kress, W.; Crayn, Darren
Abstract: Species inhabiting tropical mountaintops may be most at risk from the detrimental effects of climate change. Yet few regional assessments have critically assessed the degree of threat to species in these habitats. Here we model under three climate scenarios the current and future suitable climate niche of 19 plant species endemic to tropical mountaintops in northeast Queensland, Australia. The suitable climate niche for each of the 19 species is predicted to decline by a minimum of 17% and maximum of 100% by 2040 (mean for all species of 81%) and minimum of 46% (mean for all species of 95%) by 2080. Seven species are predicted to have some suitable climate niche space reductions (ranging from 1 to 54% of their current suitable area) by 2080 under all three climate scenarios. Three additional species are projected to retain between 0.1 and 9% of their current distribution under one or two of the climate scenarios. In addition to these declines, which are predicted to occur over the next 30 years in northeast Queensland, we discuss and outline pressing research priorities that may be relevant for the conservation of biodiversity on tropical mountaintop environments across the globe. Specifically, further research is needed on thermal tolerances, acclimation potentials, and physiological constraints of tropical mountaintop taxa as current species distributions are primarily determined by climatic factors. Highlights: We modelled future habitat suitability for 19 mountain-top plant species. We simulated 3 climate change scenarios for 2040, 2060, and 2080. Rapid declines in suitable habitat were inferred for all species by 2040. Average inferred loss of suitable habitat across all species by 2080 is 95%. We highlight climate change research gaps pertinent to conservation of tropical montane environments.